The relevance of the cross-wavelet transform in the analysis of human interaction – a tutorial - Issartel, Johann; Bardainne, Thomas; Gaillot, Philippe; Marin, Ludovic (Frontiers in Psychology, 2015)
This article sheds light on a quantitative method allowing psychologists and behavioral scientists to take into account the specific characteristics emerging from the interaction between two sets of data in general and two individuals in particular. The current article outlines the practical elements of the Cross-Wavelet Transform (CWT) method, highlighting WHY such a method is important in the analysis of time-series in psychology. The idea is 1) to bridge the gap between physical measurements classically used in physiology - neuroscience and psychology; 2) and demonstrates how the CWT method can be applied in psychology. One of the aims is to answer three important questions WHO could use this method in psychology, WHEN it is appropriate to use it (suitable type of time-series) and HOW to use it. Throughout these explanations, an example with simulated data is used. Finally, data from real life application are analyzed. This data corresponds to a rating task where the participants had to rate in real time the emotional expression of a person. The objectives of this practical example are i) to point out how to manipulate the properties of the cross-wavelet transform method on real data ii) to show how to extract meaningful information from the results and iii) to provide a new way to analyze psychological attributes.